The impact of macroeconomic policies on Tunisian current account, an ARDL approach. (15th December 2021) - Farhoud, Hager; Taleb, Lotfi
During 1980-2010 Tunisian current account deficit was persistent and worsens between 2011-2018 following the Jasmine revolution of 2011 and contribute to slow down country growth and development. The objective of this study is: 1) to examine the linkage between persistent Tunisian current account deficit and a broad set of macroeconomic variables related to fiscal, monetary and trade policies between 1980-2018; 2) enlighten policy makers in their decision-making process related to the adjustment mechanisms. Based on ARDL approach, the key findings of this study show robust empirical evidence of short and long-run effects of fiscal and monetary policies, while the effect of trade policy is only apparent in the short-term. Therefore, we conclude that, in the short-term, both a tight monetary policy and a balanced fiscal budget are necessary to adjust the current account balance. However, these reforms are not sufficient; making the Tunisian current account deficit sustainable requires structural changes to the economy over the long-term.